Fractured reservoirs - Lonergan, Lidia (Geological Society special publication ;, 2007)
Fractured reservoirs contain a significant proportion of the global hydrocarbon reserves; however, they commonly exhibit unpredictable and extreme production behaviour. This book presents an overview of current techniques and the latest technologies used to understand and exploit fractured reservoirs.